2020
DOI: 10.1186/s12951-020-00737-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PLA/chitosan nanoscaffolds containing cod liver oil and experimental diabetic wound healing in male rats study

Abstract: Diabetes mellitus is one of the most common metabolic disorders. One of the important metabolic complications in diabetes is diabetic foot ulcer syndrome, which causes delayed and abnormal healing of the wound. The formulation of nanoscaffolds containing cod liver oil by altering the hemodynamic balance toward the vasodilators state, increasing wound blood supply, and altering plasma membrane properties, namely altering the membrane phospholipids composition, can be effective in wound healing. In this study, e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…The cod liver oil loaded PLA/CS nanofiber membrane was prepared by uniaxial electrospinning, which was used to treat diabetic mice wounds. Wound experimental results of diabetic mice showed that after 14 d, the wound healing rate of the fiber group was 94.5%, which was much higher than that of the free cod liver oil group (40%) and the untreated diabetic wound group (13%) [97].…”
Section: Drugs/synthetic Polymer/natural Polymer Electrospun Fibersmentioning
confidence: 77%
“…The cod liver oil loaded PLA/CS nanofiber membrane was prepared by uniaxial electrospinning, which was used to treat diabetic mice wounds. Wound experimental results of diabetic mice showed that after 14 d, the wound healing rate of the fiber group was 94.5%, which was much higher than that of the free cod liver oil group (40%) and the untreated diabetic wound group (13%) [97].…”
Section: Drugs/synthetic Polymer/natural Polymer Electrospun Fibersmentioning
confidence: 77%
“…With the promising siRNA uptake results described above, we then explored whether PM1(GT/siMMP-9 10 ) hydrogel can promote diabetic wound healing. The skin wound model in rats used in this study is a validated and widely used model to evaluate treatments for wound healing [ 36 , 37 ]. The quantitative analysis of the wound area over time showed that wounds of the non-diabetic group healed dramatically faster ( P < 0.05) than the diabetic group when both were treated with PBS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PM1(GT/siMMP-9 10 ) hydrogel reduces MMP-9 expression and promotes wound healing With the promising siRNA uptake results described above, we then explored whether PM1(GT/siMMP-9 10 ) hydrogel can promote diabetic wound healing. The skin wound model in rats used in this study is a validated and widely used model to evaluate treatments for wound healing [34,35]. The quantitative analysis of the wound area over time showed that wounds of the non-diabetic group healed dramatically faster (P < 0.05) than the diabetic group when both were treated with PBS (Fig.…”
Section: In Vitro Release Pro Les Of Gt/sifam From Hydrogelsmentioning
confidence: 93%